2015
DOI: 10.1089/gtmb.2015.0058
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs7041 and rs4588 Polymorphisms of the Vitamin D Binding Protein and the rs10741657 Polymorphism of CYP2R1 with Vitamin D Status Among Jordanian Patients

Abstract: The rs70141657G/A of CYP2R1 and rs7041T/G and rs4588C/A of vitamin D binding protein genetic polymorphisms were associated with increased risk of vitamin D deficiency among apparently healthy Jordanians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
7
35
0
Order By: Relevance
“…However, a significant fraction of inter-individual variability in serum 25-OHD is not explained by these factors. Epidemiological studies provide robust evidence that genetic factors contribute substantially to an individual's vitamin D status [117][118][119][120][121][122][123][124][125][126]. Differences in the prevalence of vitamin D deficiency among different ethnic groups can be explained at least in part by genetic variants that affect vitamin D metabolism.…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…However, a significant fraction of inter-individual variability in serum 25-OHD is not explained by these factors. Epidemiological studies provide robust evidence that genetic factors contribute substantially to an individual's vitamin D status [117][118][119][120][121][122][123][124][125][126]. Differences in the prevalence of vitamin D deficiency among different ethnic groups can be explained at least in part by genetic variants that affect vitamin D metabolism.…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“… 22 Lafi et al have also reported an association of VDBP polymorphism with increased risk of vitamin D deficiency among healthy Jordanians. 23 On the other hand, Michos et al showed that low serum levels of 25(OH)D were associated with increased incidence of CHD among Whites, however, no interaction of 25(OH)D levels with VDBP genotypes was found in that population. 11 Similarly, VDBP genetic variants were not found to be related with CHD in Italian population.…”
Section: Discussionmentioning
confidence: 93%
“…This stage of the VD metabolic pathway is one of those in which researchers have searched for variants influencing MS, especially in CYP27B1 ; it is therefore surprising that no association was found. Associations have been described between VD deficiency and numerous genetic variants (Lafi, Irshaid, El‐Khateeb, Ajlouni, & Hyassat, ; Li et al, ; Lu et al, ; Nissen et al, ; Signorello et al, ; Slater, Rager, Havrda, & Harralson, ; Wang et al, ; Zhang et al, ) (Table S1). However, these associations do not necessarily represent increased risk of MS, as no correlation has been demonstrated between the disease and plasma VD level (Ahn et al, ).…”
Section: Discussionmentioning
confidence: 99%